Study on Internal Vibration Law and Vibration Reduction of Xiaoxiku Tunnel Blasting. (25th April 2022) - Li, Sheng-Lin; Liang, Shu-Feng; Lu, Jia-Wei
Abstract : Efficient and economical drilling and blasting method is widely used in tunnel excavation projects, but the vibration problem caused cannot be ignored. The blasting vibration in the near area directly damages the surrounding rock and supporting structure, and the vibration in the middle and far area affects the stability of the surrounding rock, the primary support, and even the secondary lining. Based on the blasting excavation of Xiaoxiku tunnel, blasting vibration tests were carried out. In addition, the measured data were analyzed by using nonlinear regression and Fourier transform of Sadowski formula. According to the interference vibration reduction method, the blasting vibration of group holes is analyzed, and the results provide a reference for blasting design optimization of Xiaoxiku tunnel or similar soft rock tunnel. The results showed that the blasting vibration test data showed that the peak vibration velocity generated by the blasting of cut hole is the largest. Based on the measured vibration waveform of single-hole blasting, MATLAB software is used to carry out superposition operation, so as to determine the best delay time of single-hole continuous blasting vibration reduction, and the value is calculated as 7 ms. According to the superposition operation results, the experiments of the cut area under different delay intervals were carried out. The measurement vibration waveform showed that the peak vibration velocity is the minimum when the delay interval is 7 ms. The actual measurement results are the same as the calculation results. The measured blasting waveform distribution is relatively uniform, and the vibration duration is moderate. The vibration speed decreases, while the main frequency increases.